The Victorian painting of modern life - Fletcher, Pamela M. (British art: histories and interpretations since 1700, 2025)
"This text offers a comprehensive and tightly focused account of the emergence and flourishing of British modern-life paintings at midcentury. Contemporary subjects were new and risky in the late 1840s and early 1850s; immensely popular and much debated by 1858; and already falling out of fashion by the mid-1860s. The book follows this story chronologically, moving from the anxious attempts by young artists such as William Powell Frith and William Holman Hunt to capture modern life in a visual language that conveyed both the literal and emotional truths of contemporary experience, through the new genre's explosion into popularity in the later 1850s and early 1860s, and the critical debates (and changing fashions) that led to its diminishment by the end of that decade. The book will be of interest to scholars working in art history, British studies, visual culture, exhibition culture, museum studies and the sociology of art"